Analisis Relasi Makna Dalam Lirik Lagu ‘Runtuh’ Karya Feby Putri Dan Fiersa Besari - Sianipar, Ratna Lolane; Sigab, Ribka Elstin; Siagian, Arlin Septia Basana; Pasaribu, Kristin Dwi Amsari; Puteri, Anggia (Journal of Innovative and Creativity, 2026)
This study aims to analyze the relationship of meaning contained in the lyrics of the song "Runtuh" by Feby Putri and Fiersa Besari. This study uses a qualitative method with a descriptive approach. The data in this study is in the form of words or phrases in song lyrics that contain meaning relationships. The source of the research data came from the lyrics of the song "Runtuh" which was analyzed in depth. The data collection technique is carried out through documentation techniques and literature review by reading and observing the lyrics of the song to find the form of meaning relationships. The results of the study show that in the lyrics of the song "Runtuh" there are several types of meaning relationships, namely synonyms, antonyms, hyponyms, polysemimes, and homonyms. The use of these meaning relationships shows that the choice of words in song lyrics not only serves as an aesthetic element, but also strengthens the emotional meaning that the song creator wants to convey. Through these meanings, song lyrics are able to describe feelings of fragility, sadness, inner exhaustion, and the process of self-acceptance experienced by a person in facing the pressures of life.